Evaluation of patients with coronary artery disease - Caobelli, F.; Pizzocaro, C.; Paghera, B.; Guerra, U. P. (Nuklearmedizin - NuclearMedicine, 2013)
Quantification of myocardial perfusion scintigraphy is often performed to assist physicians in detecting coronary artery disease (CAD). Modern software and hardware packages provide improvements able to shorten scan time and/or reduce administered activity, without compromising image quality in radionuclide myocardial perfusion imaging (MPI). Recently, multifocal collimators were introduced with dedicated reconstruction software, named IQ-SPECT, able to shorten considerably scan time. The aim of our study was to compare this new protocol to the already validated standard ones. Patients, methods: We enrolled 43 patients with suspected or diagnosed CAD. All patients underwent a two-days protocol radionuclide myocardial perfusion scan at rest and after a standard stress test (exercise or dipyridamole) after administering 99mTc-tetrofosmin. Images were acquired on a 2-head gamma camera and reconstructed with attenuation correction. All the images were scored using a 17-segments model by three experienced physicians, blind to clinical data and to acquisition and processing modality. Results, conclusion: No significant differences were recorded in perfusion scores on paired t-test and Wilcoxon among the full-time images reconstructed with standard protocol or IQSPECT, both overall on a 17-segments evaluation and when considering different territories of distribution. MPI with IQ-SPECT protocol can be acquired at about a quarter scan time without disagreement compared to full time scan acquisition performed with standard protocols.
Keywords: Coronary artery disease; 99mTc tetrofosmin SPECT/CT; IQ-SPECT; low counts acquisition; myocardial perfusion imaging